KAJIAN PENERAPAN CORPORATE UNIVERSITY DALAM PENGEMBANGAN KOMPETENSI SUMBER DAYA MANUSIA APARATUR SIPIL NEGARA - Victor Tulus Pangapoi Sidabutar (Jurnal Ilmu Pemerintahan Widya Praja, 2020)
The ease of doing business in Indonesia in 2019 has increased but the ranking only represents Jakarta and Surabaya and the overall value of Indonesia's competitiveness is still below expectations to attract foreign investors. This is because public organizations in Indonesia are considered inefficient, bureaucratic, less transparent, and have a high level of corruption. In terms of competence, there are differences in the ability of the State Civil Service Apparatus (ASN) in each region so that it is necessary to increase the ability of ASN to be able to deal with changes and developments in the world that is growing so fast and more rapidly. This is where the important role of ASN’s training units in the development of Human Resources (HR) in producing "world-class" bureaucrats. Existing training units are required to conduct training related to career development and personnel planning. For this reason, the training units must be transformed into a Corporate University (CU) which is a management tool designed to help organizations achieve their strategic goals by carrying out activities that encourage individuals and organizational learning and knowledge. In its formation, it is necessary to pay attention to the five stages in the development and implementation of CU, namely the initial diagnosis, the development of educational programs, the development of educational programs, the development and implementation of Learning Management Systems and finally the strengthening of knowledge of CU and the release of the formation of CU. Constraints in the application of CU can occur due to the mentality and moral degradation of ASN that has occurred and passed down by the previous generation. Therefore, demanded support from leaders who are open-minded and free from a silo mentality.